Express-method for assessing the quality of endodontic treatment of root canal by laser fluorescence (Эндодонтия Today)
The article investigates the effectiveness of chemical treatment of root canals. In an experiment conducted on 52 root canals of 37 extracted teeth, the effectiveness of the method of laser fluorescence diagnosis (LFD) for endodontic treatment was confirmed. There have also been found most effective antiseptic preparations used for chemical treatment – 3% hydrogen peroxide, nitric oxide treated 3% hydrogen peroxide in combination with 5% sodium hypochlorite. An algorithm for applying the method of LDF during mechanical and chemical treatment of root canals is suggested.